Self-reported hypoglycemia and associated factors among patients living with T1D s at University of Gondar Comprehensive Specialized Hospital, Northwest, Ethiopia: a cross-sectional study - Worku, Yilkal Belete; Tekle, Masho Tigabe; Bekalu, Abaynesh Fentahun; Simegn, Mulat Belay (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundHypoglycemia is a major public health problem that negatively influences blood glucose control in the treatment of type 1 diabetes. It has more severe clinical and economic effects in patients living with T1D patients. However, real-world clinical evidence of reported hypoglycemia is limited. Thus, the purpose of the study was to determine the prevalence of self-reported hypoglycemia and its associated factors among patients living with T1Dat the University of Gondar Comprehensive Specialized Hospital (UOGCSH).MethodsA prospective hospital-based cross-sectional study was conducted among patients living with T1D attending the ambulatory clinic of UOGCSH from November 1, 2021, to April 30, 2022. To select the study participants, a convenient sampling technique was used. Multivariable binary logistic regression was used to identify predictors of self-reported hypoglycemia. A P-value < 0.05 was considered statistically significant and reported as a 95% Confidence Interval (CI).ResultsA total of 216 patients living with T1D (mean age: 50.91 ± 18.98 years) were included. The mean duration of DM diagnosis and insulin use were 9.41 ± 8.00 and 7.10 ± 6.00 years, respectively. Self-reported hypoglycemia was prevalent among 86.6% (95% CI: 82.1-91.0) of the study participants, with 69% experiencing non-severe and 31% experiencing severe hypoglycemia. More than half of the patients, 122 (56.5%), reported experiencing four or more (≥ 4) episodes of hypoglycemia. Knowledge of insulin self-administration, specifically a low level of knowledge (AOR=4.87; 95% CI: 1.55-15.26), was significantly associated with self-reported hypoglycemia. The majority of patients living with T1D, 155 (71.8%), had impaired awareness of hypoglycemia.ConclusionSelf-reported hypoglycemia was considerably high among Patients living with T1D. Knowledge of insulin self-administration, specifically at a low level, was associated with an increased risk of reported hypoglycemia. Thus, continued health education of Patients living with T1D regarding insulin self-administration and awareness of hypoglycemia symptoms is necessary to prevent further complications.